Bacterial succession in oil-contaminated soil under phytoremediation with poplars. (March 2020) - Lopez-Echartea, Eglantina; Strejcek, Michal; Mukherjee, Shinjini; Uhlik, Ondrej; Yrjälä, Kim
Abstract: Petroleum hydrocarbons (PHCs) continue to be among the most common pollutants in soil worldwide. Phytoremediation has become a sustainable way of dealing with PHC contamination. We conducted the off-site phytoremediation of PHC-polluted soil from an oil tanker truck accident, where poplars were used for the phytoremediation of the oil-polluted soil in a boreal climate during a seven-year treatment. The succession of bacterial communities over the entire phytoremediation process was monitored using microbial ecological tools relying on high-throughput 16S rRNA gene sequencing. Upon the successful depletion of PHCs from soil, endophytic communities were analyzed in order to assess the complete plant-associated microbiome after the ecological recovery. The rhizosphere-associated soil exhibited different bacterial dynamics than unplanted soil, but both soils experienced succession of bacteria over time, with diversity being negatively correlated with PHC concentration. In the relatively short growing season in North Europe, seasonal variations in environmental conditions were identified that contributed to the dynamics of bacterial communities. Overall, our study proved that phytoremediation using poplar trees can be used to assist in the removal of PHCs from soils in boreal climate conditions and provides new insight into the succession patterns of bacterial communities associated with these plants. Highlights: Succession of soil bacterial communities during phytoremediation was monitored. Rhizosphere-associated soil exhibited different bacterial dynamics than bulk soil. Diversity was negatively correlated with petroleum hydrocarbon concentration. Endophytes were analyzed to assess the complete plant-associated microbiome. Poplars can be used to assist phytoremediation in boreal climate conditions.